A case study on Zakat management at Pusat Islam UTM, Skudai - Nur Qamarina binti Sharom (Graduate School of Management,International Islamic University Malaysia, 2011)
This study primarily focuses on the Zakat management as practiced in Pusat Islam Universiti Teknologi Malaysia (PIUTM), Skudai. The study specifically looks at the collection and distribution process of Zakat on income. It also examines the reporting mechanism concerning the performance of zakat collection and distribution of the organisation. In addition, the study also discusses the issues and challenges faced by the organization. A single case study method was used in which data were collected through semi-structured interviews, document reviews, informal conversations and observations. The data reveal that PIUTM collects the zakat on income from UTM' s employees and distributes some portion of asnaffisabilillah to the UTM community only. There are only three types of distribution - free food coupon scheme, self-support scheme and assistance for undergraduate association programme. The research also shows that the PIUTM has never set any indicators to measure the performance of the management of Zakat on income. This research offers insights into the role of PIUTM as a centre for zakat collection and distribution within a small locality. Based on the findings, it is suggested that PIUTM may want to consider upgrading the reporting style and follow the structure of annual reports. The research also suggests that indicators should be introduced so that the organization will achieve its objectives.